A detective's history of psychology: understanding key theories and concepts through mystery fiction - Mello-Goldner, Diane (McFarland & Company, Inc., Publishers, 2024)
"Are you captivated by detective fiction and mystery stories? Do you enjoy solving puzzles or explaining other people's behavior? Have you ever thought Miss Marple would make a good therapist or Sherlock Holmes an excellent researcher? If so, you probably have already seen the connection between detective fiction and the field of psychology. This book introduces key concepts and theories of psychology through the lens of mystery fiction. It explores the crossroads where detective fiction converges with psychology with clarity and is catered to curious readers from all backgrounds. It includes thought-provoking activities and questions to strengthen readers' deductive reasoning, critical thinking, and psychological insights, and to let their inquisitiveness guide them."--